2022
DOI: 10.1111/liv.15458
|View full text |Cite
|
Sign up to set email alerts
|

A history of variceal bleeding is associated with further bleeding under atezolizumab–bevacizumab in patients with HCC

Abstract: Background Atezolizumab–bevacizumab is the new standard for advanced hepatocellular carcinoma (HCC) but its impact on portal hypertension (PHT) is unknown. We aimed to identify predictive factors of acute variceal bleeding (AVB) and to monitor PHT parameters under treatment. Methods We conducted a prospective study including all cirrhotic patients treated with atezolizumab–bevacizumab since 2020. We performed monitoring of PHT using upper endoscopy at inclusion and at 6 months and hepatic venous pressure gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
0
15
2
Order By: Relevance
“…Some practitioners might be reluctant to start atezolizumab-bevacizumab in the setting of large EVs, in the case of red marks on EVs, in patients with vascular invasion or in the setting of curative anticoagulation. However, recent studies, including ours, did not show a higher risk of AVB in such situations but did in the case of previous AVB regardless of the delay 55,104 . Consequently, we believe that only a history of AVB is associated with a higher risk of AVB in the setting of atezolizumab-bevacizumab treatment but not large EV size, vascular invasion, or curative anticoagulation.…”
Section: Management Of Avb In Patients With Hcccontrasting
confidence: 48%
See 4 more Smart Citations
“…Some practitioners might be reluctant to start atezolizumab-bevacizumab in the setting of large EVs, in the case of red marks on EVs, in patients with vascular invasion or in the setting of curative anticoagulation. However, recent studies, including ours, did not show a higher risk of AVB in such situations but did in the case of previous AVB regardless of the delay 55,104 . Consequently, we believe that only a history of AVB is associated with a higher risk of AVB in the setting of atezolizumab-bevacizumab treatment but not large EV size, vascular invasion, or curative anticoagulation.…”
Section: Management Of Avb In Patients With Hcccontrasting
confidence: 48%
“…[103] Notably, patients with an AVB history in the last 6 months or without efficient prophylaxis for AVB were excluded from the study, and recently published real-life data showed that 14% of the patients presented with an AVB during follow-up under this new treatment. [55,104] Some practitioners might be reluctant to start atezolizumab-bevacizumab in the setting of large EVs, in the case of red marks on EVs, in patients with vascular invasion or in the setting of curative anticoagulation. However, recent studies, including ours, did not show a higher risk of AVB in such situations but did in the case of previous AVB regardless of the delay.…”
Section: General Management Of Avb In Hcc Patientsmentioning
confidence: 99%
See 3 more Smart Citations